Psychological states could affect postsurgical pain after hemorrhoidectomy: A prospective cohort study - Wang, Geng; Wu, Yuanjue; Cao, Yang; Zhou, Rui; Tao, Kaixiong; Wang, Linfang (Frontiers in Surgery, 2023)
Background Open haemorrhoidectomy is a standard procedure for grade Ⅳ hemorrhoid. Post-surgical pain is a common problem for the patients. We aim to prospectively evaluate potential factors which may affect postoperative pain among haemorrhoidectomy patients. Methods An observational study was conducted in 360 patients who had underwent Milligan-Morgan open hemorrhoidectomy. Details of the surgery and baseline information were recorded. Pre-operative anxiety and depression were analyzed via the self-rating anxiety scale 20 and self-rating depression scales 20. Post-operative pain score was performed daily after surgery until the patients was discharged. Numerical pain score was evaluated by the visual analogue scale pain score. The association between preoperative psychological states (anxiety or depression) and postoperative pain was analyzed using a generalized additive mixed model. Results 340 patients eventually provided complete data and were included in our study. The average age is 43.3 ± 14.4 years old and 62.1% of patients were female. 14.9% of patients had pre-surgical anxiety and 47.1% had pre-surgical depression. Post-surgical pain reached peak point at 1-2 days after surgery and went down to a very low level around 4-5 days after surgery. More excision of hemorrhoids could lead to more pain experience after surgery. Pre-surgical depression were associated with post-surgical pain. Patients who had pre-surgical depression had higher pain score after surgery (2.3 ± 1.9 vs 3.3 ± 1.9, p=0.025). Conclusion Preoperative depression, the amount and position of the excisional hemorrhoids are positively related to post-surgical pain.